Perception and detection of gender violence, and identification as victims: A bibliometric study - Badenes-Sastre, Marta; Expósito, Francisca (Anales de Psicología / Annals of Psychology, 2021)
This bibliometric study seeks to know and analyse the available scientific activity on the perception and detection of gender violence as well as in the identification as victims. An unlimited search was conducted in the Scopus database, finding 2,152 documents. Subsequently, the results were screened by reducing the documentary noise. The results were obtained from 1984-2020 and the final 974 documents were analysed from 465 documentary sources, 160 journals, 2,758 authors, 159 institutions, and 79 countries. The results show an increase in production in recent years, highlighting the publication of original articles. Likewise, the single authorship per country predominates, being the United States the leading country. The main objectives of the most cited documents are detection of gender-violence by healthcare personnel, assessment of the risk of recidivism through the perception of the victims, as well as the study of perceptions and attitudes of different actors towards gender-violence.